2013
DOI: 10.1007/s00779-013-0666-y
|View full text |Cite
|
Sign up to set email alerts
|

Device-Independent Architecture for ubiquitous applications

Abstract: The part of the Internet of Things composed of devices that directly interact with users has grown considerably in the past years. With new smartphones, tablets and other Internet-enabled devices that appear on the market, this trend is still increasing. However, existing application development processes and tools, designed for single device applications, do not allow developers to fully and efficiently address this opportunity. Applications are developed for a particular type of devices or a particular progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Similar use cases have also been explored recently where mobile device clouds are constructed to offer advanced sound features such as multi-channel surround sound [17], directional sound [5] and noise cancellation [11]. More such examples are also seen in the field of Internet of Things (IoT) [7]. The main challenge of ensuring the quality of user experience in immersive and interactive multi-device applications is the real-time measurement, QoE evaluation, and control of the synchronicity between media objects in an ensemble of user devices over heterogeneous networks.…”
Section: Use Case and Related Workmentioning
confidence: 99%
“…Similar use cases have also been explored recently where mobile device clouds are constructed to offer advanced sound features such as multi-channel surround sound [17], directional sound [5] and noise cancellation [11]. More such examples are also seen in the field of Internet of Things (IoT) [7]. The main challenge of ensuring the quality of user experience in immersive and interactive multi-device applications is the real-time measurement, QoE evaluation, and control of the synchronicity between media objects in an ensemble of user devices over heterogeneous networks.…”
Section: Use Case and Related Workmentioning
confidence: 99%
“…Similar use cases have also been explored recently where mobile device clouds are constructed to offer advanced sound features such as multi-channel surround sound [12] and directional sound [3]. More such examples are also seen in the field of Internet of Things (IoT) [5]. The main challenge of ensuring the quality of user experience in immersive and interactive N-Screen applications is the real-time measurement, QoE evaluation, and control of the synchronicity between media objects in an ensemble of user devices over heterogeneous networks.…”
Section: Use Case and Related Workmentioning
confidence: 99%
“…Both audio sources have nearly identical distance to the test participants, therefore any latency caused by the speed of sound is negligible. Scores given by each user are re-scaled to range [1,5]. Figures 3(a), 3(b) and 3(c) show the mean opinion score (MOS) for each clip.…”
Section: A Perception Of Non-synchronicitymentioning
confidence: 99%
“…The main difference here is the increased size of data that has to be transferred. More data to transfer could mean longer response times, but our previous research [16] showed that in analyzed scenarios DIA-based systems can still maintain proper response times to UI interactions initiated by a user, despite the increased size of transferred data.…”
Section: Ui Adaptation In Dia Systemsmentioning
confidence: 99%